An Analysis of Black Faculty in CS Research Departments: Exploring Black faculty at computer science research departments where Ph.D. programs exist. - Gilbert, Juan E.; Waisome, Jeremy A. Magruder; Smarr, Simone (Communications of the ACM, 2023)
The article focuses on Black faculty members within computer science (CS) research departments, specifically those where Doctor of Philosophy (Ph.D.) programs exist. The authors discuss the importance of diversity within the field of CS, note that Black faculty members are underrepresented, and provide a list of U.S. universities where there are Black faculty, including Howard University, the University of Florida, and Auburn University.